Problem Solving Method Management to Improve the Quality of PAI Learning - Ike Kurniati; Helmawati Helmawati; Muhibbin Syah (UIN Sunan Gunung Djati Bandung, 2021)
The development of science and technology must be balanced with an increase in the quality of learning in the world of education. The quality of learning becomes low when educators only stick to conventional teaching materials. Strengthened by the existence of Islamic Education teachers delivering teaching materials with the lecture method so that the learning process feels boring, monotonous and less attractive to students. So it is necessary to choose the right learning method in the learning process, one of which is the problem solving method. The problem solving method is interactive learning using one that can improve the quality of learning with active, innovative, creative, effective, and fun learning (PAIKEM) as well as being happy and having weight (Gembot). The purpose of this study is to determine the planning, implementation, evaluation, impact and supporting and inhibiting factors along with their solutions. With the aim of this research, the researcher asked a research question on how to manage problem solving methods to improve the quality of Islamic education learning. To clarify the background, the authors describe management, the quality of learning, problem solving methods and PAI. The description of the results of this study shows that the problem solving method in Islamic Education learning is very popular and understood by students with learning indicators using group discussions and independent tasks in completing case studies. As for infrastructure, the ability of educators and students are supporting and inhibiting factors in learning problem solving methods. The conclusion of this research is that the problem solving method is able to improve the quality of Islamic education learning with indicators of cognitive, affective and psychomotor enhancement.